Diana L. Eck. Darían: Seeing the Divine Image in India. 2a. ed.; Chambersburg, P.A., Anima Books, 1985. - Lorenzen, David N. (El Colegio de México, 1987)
Joanne Punzo Waghorne y Norman Cutler (comps.), Gods of Flesh, Gods of Stone: The Embodiment of Divinity in India, Chambersburg, P.A., Anima Books, 1985.